Implementasi Pendidikan Antikorupsi Dalam Rangka Penguatan Nilai Karakter Kejujuran Pada Peserta Didik Kelas VIII di SMP Negeri 1 Mojolaban Tahun 2022/2023 - Niken Tri Prasetyowati; Sutoyo Sutoyo; Siti Supeni (Prodi PPkn Universitas Slamet Riyadi, 2022)
The objectives of this study were to: (1) find out how the implementation of anti-corruption education in order to strengthen the value of honesty character in class VIII students at SMP Negeri 1 Mojolaban (2) find out whether the implementation of anti-corruption education is correct to strengthen the value of honesty character in class VIII students. (3) Knowing the factors that support and hinder the implementation of anti-corruption education in order to strengthen the value of the character of honesty in class VIII students.This research was conducted at SMP Negeri 1 Mojolaban. The subjects of this research include principals, vice principals, PPKn teachers, and students. The data source uses primary data sources and secondary data sources. Data was collected through interviews, observation, and documentation. The validity of the data was tested by technique triangulation and source triangulation. The research data were analyzed using a qualitative descriptive analysis technique with an interactive model. The results of the study can be concluded that: 1) SMP Negeri 1 Mojolaban has provided anti-corruption education lessons because anti-corruption education is very important to learn with anti-corruption education in the curriculum can teach students to be honest, responsible and teach things about the dangers of committing crimes. corruption, so that students in the future of our country can be free from corrupt behavior. 2) True anti-corruption education is a reinforcement of the character value of honesty. 3) there are 2 influencing factors, namely: a. supporting factors: teacher commitment, adequate school infrastructure, parental support, conducive environment, cooperation of all components, teachers working together, the role of BK teachers in dealing with students; b. Inhibiting factors: The Covid-19 outbreak, lack of motivation, differences of opinion, teachers feel overwhelmed, the ability of teachers to choose subjects, anti-corruption education has not been fully implemented, there are still some teachers who have not integrated, and students' low interest in learning.